A Longitudinal Comparison of Enrollment Patterns of Students Receiving Special Education in Urban Neighborhood and Charter Schools. (June 2017) - Waitoller, Federico R.; Maggin, Daniel M.; Trzaska, Agata
The purpose of this study is to compare and examine special education enrollment trends across disability categories and grade spans for public neighborhood and charter schools in the City of Chicago. Using multilevel longitudinal data analysis methods, we examined annual school enrollment and demographic reports. Our findings indicated that neighborhood schools serve significantly higher proportions of students receiving special education services (SRSE) than charter schools at the aggregate grade level (i.e., elementary and high school enrollments) and at each grade level. In addition, we found that charter schools enroll equal or significantly higher proportions of students with learning disabilities (LD), speech and language impairments (SLI), other health impairments (OHI), and emotional disturbance (ED), and substantially smaller proportions of students with autism, sensory impairments (SI), and intellectual disabilities (ID), when compared with neighborhood schools. However, we found that these differences vary between grade levels. We discuss the implications of these findings for policies affecting charter school authorization and contract renewal, and for policies establishing special education enrollment targets in charter schools.